Ecotoxicity Analysis and Risk Assessment of Nanomaterials for the Environmental Remediation - Thakur, Abhinay; Kumar, Ashish (Macromolecular symposia., 2023)
The evolution of a safe‐by‐design work premised on nanotechnology relies on the regulation of healthcare, safety, and environmental concerns throughout the manufacture, handling, preservation, assimilation, and disposal of nanomaterials. The practically infinite potential for nanoparticles to be functionalized, chemically interacted with, and added to new products necessitates a new management method for the safe and hazard‐free application of nanotechnology. Nanomaterials (NMs) like silver NMs and nanomaterial composites have a limited quantity of accurate toxicity and ecotoxicological evidence, which has a severe effect on the ecosystem. Due to the intricate and cross‐disciplinary architecture for several components and processes at the nanoscale, risk assessment in the field of nanotechnology necessitates an integrated interdisciplinary approach. In this review, the study begins by providing an insight into the general characteristics of nanoparticle synthesis and ecotoxicity assessments using a variety of green solutions. In addition, there are sections on safety protocols that encourage industrialists to use NMs more effectively in their operations.